IDENTIFYING THE SLIP OF TONGUE IN EFL CLASSROOM: ONE ERROR THAT BLOCKED STUDENTS' FLUENCY IN SPEAKING - Enni Akhmad Daud; Ali Imron Mustofa (LP2M IAIN Sultan Amai Gorontalo, 2018)
One indicator of being able to speak is having good pronunciation. Slip of tongue is one factor that is blocking good pronunciation. This research investigates the types of slip of togue which doe by students I prooucig English as a foreign language. There were 5 students of seventh semester at English Education Program academic year 2017/2018 IAIN Sultan Amai Gorontalo, as the subjects of this research. It used qualitative method in order to describe the kinds of error on students’ pronunciation, especially when they are in slip of tongue. Audio recording was used to identify the students’ pronunciation, data analyzing was done by transcribing their error pronunciation. The result shown from six of eight types of slips of the tongue occurred on students’ pronunciation, namely Shift, Anticipation, perseveration, addition, deletion and substitution, the main slip of tongue occurred on students’ pronunciation was substitution.